COVID-19 and tourist mobility at destinations: a literature review and emerging research agenda - Viana-Lora, Alba; Domènech, Antoni; Gutiérrez, Aaron (Journal of Tourism Futures, 2023)
PurposeThis paper aims to review conceptual and empirical studies that analyse the impact of the pandemic on mobility and tourism behaviour at destinations in order to identify proposals, forecasts and recommendations to guide the future research agenda on the subject.Design/methodology/approachThis study used a systematic literature review to synthesise information from scientific articles published in journals indexed in the Web of Science database related to tourism mobility at destinations during the COVID-19 pandemic.FindingsThis article found that, according to the existing literature, the COVID-19 pandemic is acting as a catalyst for the sustainable transition of tourism. Although the findings reveal a lack of empirical research on the impact of the pandemic on tourism mobility at destinations, the article synthesizes the short- and long-term impacts of the pandemic and sets out the future research agenda on tourist mobility at destinations.Originality/valueTo the best of the authors' knowledge, this is the first systematic review of the impact of the pandemic on mobility and tourism behaviour at destinations that attempts to describe the emerging challenges and the agenda for future research.